Development and demographic parameters of Fall Armyworm (Spodoptera frugiperda J.E. Smith) when feeding on rice (Oryza sativa) - Ali, Md Panna; Haque, Sheikh Shamiul; Hossain, Mohammed Mosaddeke; Bari, Md Nazmul; Kabir, Mir Md Moniruzzaman; Roy, Tapon Kumar; Datta, Juel; Howlader, Mohammad Tofazzal Hossain; Alam, Syed Nurul; Krupnik, Timothy J. (Springer, 2023)
Fall Armyworm (FAW), Spodoptera frugiperda (Lepidoptera: Noctuidae), native to the Americas, is a polyphagous insect pest feeding on more than 350 plant species. We studied the developmental and demographic parameters of the maize (Zea mays) strain of FAW on rice (Oryza sativa), and compared the results with its prime host, maize. The developmental period from egg to adult among rice varieties did not differ significantly; however, it did differ significantly between rice and maize, as feeding on rice rather than maize extends development duration of FAW larvae by 15.15%. FAW larvae collected and reared on maize were found to be of significantly higher weight than those reared on rice at two sequential dates of their development; pupal weight however was observed as statistically similar between these two host crops. Regardless of the host, female adults always emerged before males; in maize, female FAW appeared 3.36 days earlier than males. Females derived from rice had longer pre-oviposition periods and shorter oviposition ones than those derived from maize. In rice and maize, the age-specific fecundity rate (mx) peaked at 40 days and 33 days, respectively. When the Fall Armyworm consumed maize instead of rice, there was an increase in the reproduction rate (R0), the intrinsic rate of natural increase (rm), and the finite rate of increase (λ). For instance, when FAW fed on rice, the rm value was 0.121, whereas it rose to 0.173 when FAW fed on maize. Feeding on rice instead of maize resulted in significantly longer mean length of generation (tG) and doubling time (tD) for the fall armyworm (FAW). This suggests that it took a longer time for the FAW population to double when it was fed rice under controlled greenhouse conditions. In summary, our research suggests that FAW can survive and complete its life cycle on rice plants and on multiple varieties of rice in Bangladesh. However, field verification is necessary before drawing strong conclusions as to the risk posed by FAW in rice. This requires additional studies of FAW and associated insect community dynamics under non-controlled conditions and in the context of multi-species interactions in Asian rice fields.